Adherence and Continued Participation in a Wellness Class for Individuals with Disabilities. (February 2019) - Ware, Megan Elizabeth; deMarrais, Kathleen B; McCully, Kevin K
Background: For individuals with disabilities, adherence and participation in wellness programs is a challenge. Adherence and participation were explored in a wellness class for people with disabilities. Objective: Understand what factors impact participant adherence and participation in the wellness class. Methods: Eight wellness class participants, who have been in the class for 6 to 36 months, were chosen for qualitative interviews. Interview responses were coded and analyzed for overarching themes. Results: A total of 77 codes were obtained from interview data. The primary theme identified from the codes was related to social interaction with the student-trainers, divided into subthemes of social accountability, motivation, supporting classroom environment, and participant-student interaction. Conclusion: The primary factor influencing adherence and participation was related to social interaction with student-trainers. These results suggest that social interaction can play a major role in continued participation in exercise as well as exercise adherence.